Impacts of Horizontal Resolution of the Lateral Boundary Conditions and Downscaling Method on the Performance of RegCM4.6 in Simulating the Surface Climate Over Central‐Eastern China. Issue 8 (8th August 2022) - Xu, Xiaoke; Huang, Anning; Huang, Qian; Zhang, Yan; Wu, Yang; Gu, Chunlei; Cai, Shuxin; Zhu, Xueyan
Abstract: This study investigated the impacts of horizontal resolution of lateral boundary condition (LBC) and downscaling method on the performance of RegCM4.6 in simulating the 2 m air temperature and precipitation over central eastern China. Two groups of experiments (direct downscaling experiments using LBC derived from the same reanalysis data but with different horizontal resolutions [0.75°, 1.5°, and 2.5°] and double‐nested downscaling experiment) with the model horizontal resolution of 20 km over central eastern China have been carried out. Results show that the direct downscaling experiments consistently outperform the double‐nested experiment to simulate the 2 m air temperature and precipitation over central eastern China, suggesting that adopting the direct downscaling method is appropriate to simulate the surface climate over central eastern China. Meanwhile, the direct downscaling experiments driven by the LBC derived from the reanalysis data with the horizontal resolution ranging from 0.75° to 2.5° display very comparable performance with a little better performance by adopting the LBC derived from the reanalysis data of much finer resolution. Further mechanism analysis indicates that much larger errors of LBC produced by the double‐nested downscaling method lead to the positive pressure biases and negative biases of water vapor convergence flux over Jianghuai Valley, which contribute to the much larger biases of precipitation and 2 m air temperature in the double‐nested downscaling experiment compared to the direct downscaling experiments. This study emphasizes that the direct downscaling method is superior to the double‐nested downscaling method for the simulations of 2 m air temperature and precipitation over central eastern China. Key Points: Direct downscaling method is more suitable to simulate the surface climate over central eastern China than double‐nested approach Limited impact of the horizontal resolution of reanalysis data for lateral boundary condition generation on the model performance by adopting direct downscaling